2018
DOI: 10.1093/cercor/bhy090
|View full text |Cite
|
Sign up to set email alerts
|

Possible Neurobiological Underpinnings of Homosexuality and Gender Dysphoria

Abstract: Although frequently discussed in terms of sex dimorphism, the neurobiology of sexual orientation and identity is unknown. We report multimodal magnetic resonance imaging data, including cortical thickness (Cth), subcortical volumes, and resting state functional magnetic resonance imaging, from 27 transgender women (TrW), 40 transgender men (TrM), and 80 heterosexual (40 men) and 60 homosexual cisgender controls (30 men). These data show that whereas homosexuality is linked to cerebral sex dimorphism, gender dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 96 publications
7
65
1
Order By: Relevance
“…This result fits with previous longitudinal studies that have shown reductions of cortical thickness in TW pre to post CHT [16]. Structural and functional alterations of the insula have consistently been associated with transgender compared to CG individuals [45,28,29,10,13]. The insula is associated with body and self-perception.…”
Section: Discussionsupporting
confidence: 90%
“…This result fits with previous longitudinal studies that have shown reductions of cortical thickness in TW pre to post CHT [16]. Structural and functional alterations of the insula have consistently been associated with transgender compared to CG individuals [45,28,29,10,13]. The insula is associated with body and self-perception.…”
Section: Discussionsupporting
confidence: 90%
“…Of note, sexual orientation may also contribute to prior discrepancy. Guillamon et al (2016) and Savic and colleagues (Manzouri & Savic, 2019) hypothesized that sexual orientation may significantly contribute to the discrepant findings as it was not well-controlled for in previous work (e.g., Luders et al, 2009;Mueller, Landre, et al, 2017) or, instead, the sample size was very small (Simon et al, 2013). One strength of the present study was that both trans- The second objective aimed to examine how divergence in anatomical findings can be further reduced, especially when dealing with populations with small prevalence rates.…”
Section: Discussionmentioning
confidence: 85%
“…The present findings demonstrate that a change in the appearance of one's own body can sufficiently perturb the sense of own gender. 13 A thorough reader might ask: if the perception of one's own body is so critical for gender identity, then how can these two aspects remain in conflict for a prolonged period of time in transgender individuals? First, our results should not be treated as evidence that the perceived bodily sex is the only factor that shapes the sense of own gender; instead, this sense is a complex phenomenon that is constructed from multiple factors1,2,5-7.…”
Section: Discussionmentioning
confidence: 99%